The earned income tax credit, health, and happiness - Casey Boyd-Swan; Chris M. Herbst; John Ifcher; Homa Zarghamee (Institute for the Study of Labor (IZA), 2013)
This paper contributes to the small but growing literature evaluating the health effects of the Earned Income Tax Credit (EITC). In particular, we use data from the National Survey of Families and Households to study the impact of the 1990 federal EITC expansion on several outcomes related to mental health and subjective well-being. The identification strategy relies on a difference-in-differences framework to estimate intent-to-treat effects for the post-reform period. Our results suggest that the 1990 EITC reform generated sizeable health benefits for low-skilled mothers. Such women experienced lower depression symptomatology, an increase in self-reported happiness, and improved self-efficacy relative to their childless counterparts. Consistent with previous work, we find that married mothers captured most of the health benefits, with unmarried mothers' health changing very little following the 1990 EITC reform.
Keywords: I1; J00; 330; Earned Income Tax Credit (EITC); happiness; health; subjective well-being